Application of thin layer and column chromatography in monitoring the synthesis of α- tocopheryl-lysine ester - Gagić Žarko; Ivković Branka; Nikolić Katarina; Agbaba Danica (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2014)
Vitamin E comprises of two families of compounds, tocopherols and tocotrienols. It is well known for its antioxidant activity, but recently special attention is paid to the use of vitamin E and its derivatives in the prevention and the treatment of cancer. Various derivatives of vitamin E are synthesized, which exhibit antiproliferative activity. It has been shown that the α-tocopherol ester with the amino acid lysine exhibits improved antiproliferative activity on MCF-7 breast cancer cell line as compared to commercially available preparations. The first stage was the synthesis of α-tocopherol ester with di-Cbz-lysine. Synthesis of ester was monitored by thin layer chromatography (mobile phase: n-hexane-ethyl acetate 3: 1,2 v/v) and the purification of product was done by dry flash column chromatography and by preparative plate chromatography (mobile phase: n-hexane-ethyl acetate 3: 1,2 v/v). In the second stage, Cbz protecting groups were removed by catalytic hydrogenation. The final product α- tocopheryl-lysine ester was detected by TLC (mobile phase: dichloromethane-methanolammonia 9 : 0,9 : 0,1 v/v).